2016
DOI: 10.1080/03601234.2016.1170540
|View full text |Cite
|
Sign up to set email alerts
|

Maize, switchgrass, and ponderosa pine biochar added to soil increased herbicide sorption and decreased herbicide efficacy

Abstract: Biochar, a by-product of pyrolysis made from a wide array of plant biomass when producing biofuels, is a proposed soil amendment to improve soil health. This study measured herbicide sorption and efficacy when soils were treated with low (1% w/w) or high (10% w/w) amounts of biochar manufactured from different feedstocks [maize (Zea mays) stover, switchgrass (Panicum vigatum), and ponderosa pine (Pinus ponderosa)], and treated with different post-processing techniques. Twenty-four hour batch equilibration meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 48 publications
1
4
0
2
Order By: Relevance
“…For example, increasing the temperature from 15 to 35°C reduces N 2 O and CO 2 solubility in water 42 and 43%, respectively. Smith et al (1998) and Clay et al (1990) had similar results and reported that GHG emissions increased with soil temperature. However, there were distinct differences between the N 2 O-N and CO 2 -C emissions pattern.…”
Section: Results and Discussion Nitrous Oxide And Carbon Dioxide Emissupporting
confidence: 70%
See 1 more Smart Citation
“…For example, increasing the temperature from 15 to 35°C reduces N 2 O and CO 2 solubility in water 42 and 43%, respectively. Smith et al (1998) and Clay et al (1990) had similar results and reported that GHG emissions increased with soil temperature. However, there were distinct differences between the N 2 O-N and CO 2 -C emissions pattern.…”
Section: Results and Discussion Nitrous Oxide And Carbon Dioxide Emissupporting
confidence: 70%
“…Biochar has been reported to sorb other organic compounds. For example, Clay et al (2016) reported that the biochar used in this experiment reduced the amount of positive and negatively charged herbicides in the soil solution. Prommer et al (2014) had similar results and reported that biochar increased total organic C and decreased dissolved organic C, whereas Jones et al (2011) reported that biochar increased simazine (6-chloro-N,N'-diethyl-1,3,5-triazine-2,4-diamine) sorption, which reduced its leaching and degradation.…”
Section: Soil Inorganic Nitrogen and Nitrificationmentioning
confidence: 99%
“…The ability of biochar to lower the bioavailability of pesticides in soils has been widely reported [29,175]. Clay et al [176] showed that biochar application can significantly increase herbicide sorption but reduce herbicide efficacy. The adsorption of pesticide on biochar mainly depends on the properties of biochar used for remediation.…”
Section: Pesticidementioning
confidence: 99%
“…Por otro lado, el BC ha influido positivamente sobre las poblaciones y la actividad de los microorganismos benéf icos para las especies vegetales (Akhtar et al, 2015;Liao et al, 2016;Tripti et al, 2017). Por consiguiente, impactos positivos sobre la germinación (Clay et al, 2016), crecimiento y desarrollo de los cultivos (Pérez- Salas et al, 2013;Fawad et al, 2017;Liu et al, 2017a), y producción de biomasa pueden ser generados (Lou et al, 2016). Esto podría traducirse en mejores rendimientos de los cultivos (Mackie et al, 2015;Dai et al, 2016;Plaza et al, 2016;Zhang et al, 2016b;Mia et al, 2017;Trupiano et al, 2017).…”
Section: Introductionunclassified
“…El uso del BC ha ido en aumento en diversas partes del mundo (Ajayi et al, 2016); sin embargo, más estudios sobre sus efectos son necesarios (Hammer et al, 2015;Wang et al, 2015;Ajayi et al, 2016;Aller, 2016;Prapagdee y Tawinteung, 2017;Seehausen et al, 2017), puesto que sus propiedades no serán siempre las mismas, debido a que dependerán de las características de la materia prima y las condiciones de la pirólisis (Clay et al, 2016;Laghari et al, 2016;Tripathi et al, 2016). Asimismo, los efectos del BC sobre los cultivos estarán influenciados por las cantidades aplicadas, el tipo de suelo y la especie vegetal cultivada (Cely et al, 2015); de tal forma que, así como pueden encontrarse efectos benéf icos, también podrían encontrarse efectos nulos o desfavorables (Mackie et al, 2015;EscalanteRebolledo et al, 2016;Plaza et al, 2016;Smebye et al, 2016;Trupiano et al, 2017).…”
Section: Introductionunclassified